2017
DOI: 10.5539/jas.v9n3p193
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Use and Protein Yield of Two Maize Cultivars in Cohesive Tropical Soil

Abstract: One major challenge to developing sustainable family farms in tropical regions is increasing nitrogen use efficiency. The aim of this study was to evaluate the combined effects of leguminous residues of low-and high-quality on nitrogen uptake, as well as on content of protein of a Quality Protein Maize (QPM) and of a hybrid maize in a tropical sandy loam soil. The experimental design consisted of randomized blocks with four replicates in a 6 × 2 factorial and six treatments: Gliricidia + Clitoria (GC); Glirici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Previous studies also showed that N demand post-silking increases significantly when the grain yield exceeded 15 Mg ha −1 (Ding et al, 2005;Huang et al, 2007;Ciampitti and Vyn, 2013a), which was in accordance with our observation. Adequate N uptake during grain filling reduces N mobilization from the vegetative organs (Fageria and Baligar, 2005), which may result in delayed leaf senescence, prolonged dry matter accumulation, and higher grain yield (Rajcan and Tollenaar, 1999;Marques et al, 2017). Therefore, adequate N supplementation and uptake by plants during grain filling in this study may have been a primary factor contributing to the highest yield occurring with high plant density, which is in accordance with our hypothesis.…”
Section: Discussion Nitrogen Uptake and Grain Yieldsupporting
confidence: 87%
See 1 more Smart Citation
“…Previous studies also showed that N demand post-silking increases significantly when the grain yield exceeded 15 Mg ha −1 (Ding et al, 2005;Huang et al, 2007;Ciampitti and Vyn, 2013a), which was in accordance with our observation. Adequate N uptake during grain filling reduces N mobilization from the vegetative organs (Fageria and Baligar, 2005), which may result in delayed leaf senescence, prolonged dry matter accumulation, and higher grain yield (Rajcan and Tollenaar, 1999;Marques et al, 2017). Therefore, adequate N supplementation and uptake by plants during grain filling in this study may have been a primary factor contributing to the highest yield occurring with high plant density, which is in accordance with our hypothesis.…”
Section: Discussion Nitrogen Uptake and Grain Yieldsupporting
confidence: 87%
“…2A, 3A, and 3B). Adequate N uptake during grain filling reduces N mobilization from the vegetative organs (Fageria and Baligar, 2005), which may result in delayed leaf senescence, prolonged dry matter accumulation, and higher grain yield (Rajcan and Tollenaar, 1999;Marques et al, 2017). Furthermore, we found that the slope of the relationship between N uptake post-silking and maize grain yield (y = 13.254e 0.151x ) was greater than that of N uptake at silking and grain yield (y = 10.583x + 19.584), and thus the N uptake post-silking may be more important (Mueller and Vyn, 2016).…”
Section: Discussion Nitrogen Uptake and Grain Yieldmentioning
confidence: 99%
“…Larger differences between control and CL treatments in 2013 suggest greater effects of this biomass combination when lower values of rainfall index occur, which may be important to meet the challenge of cooling crops under global warming. According to Marques et al, (2017) , the effects of residues of different quality on maize grain yield in the tropics vary from year to year due to differences in the potential of residues to maintain soil water availability in drier years.…”
Section: Discussionmentioning
confidence: 99%